Isolation and characterization of marine sediment bacteria capable of biocatalyzing bromination of indole, indigo, and biphenyl - Galarion, Luiza H. (Institute of Biology, College of Science, University of the Philippines Diliman, 2013)
The presence of naturally occurring halometabolites in the marine environment has led to studies focusing on the detection of enzymes and organisms capable of biocatalyzing halogenation reactions such as the addition o chlorine, bromine, and iodine. Several important halogenated compounds are now chemically derived but organic production is preferred as it is simpler and more convenient. In this study we isolated two marine sediment bacteria (WK7 and WK12) from Mokpo-si, Jeollanam-do, South Korea with 99% sequence similarity to Pseudoalteromonas issachenkonii and Shewanella marisflavi by16s rDNA sequence analyses. These bacteria were capable of biohalogenation activity using the monochlorodimedone (MCD) assay.This is the first report on marine sediment bacteria capable of biocatalyzing bromination of mentioned substrates.